Optimal Power Generation from Bagasse in a Sugarcane Plant using PSO Algorithm Compared to SQP Algorithm - Mohammad Askari Khanabadi; Imaneh Dehghani; Shahrokh Shojaeian (Majlesi Journal of Electrical Engineering, 2024)
Due to the high amounts of sugarcane residue or bagasse which was produced by sugarcane plants in Iran, this study was aimed to optimize power generation from bagasse biomass in sugarcane plants using Particle Swarm Optimization (PSO) algorithm by data obtained from several case studies which had been simulated with SQP (Sequential quadratic programming) algorithm. In these studies, bagasse containing 50% moisture content (MC) alone or with fossil fuels, as well as bagasse with a moisture content of 40% and 30% with fossil fuels were used. Optimization values showed that 20% decrease in bagasseâs MC caused 55.6% increase in power generation efficiency, 36.3% reduction in gas emissions as well as 100% bagasse saving. PSO showed similar results to SQP and it seems that it is a proper algorithm than SQP. Therefore, if the bagasse is more dried by solar energy to lower MC, the greater efficiency of power generation is obtained.